Pelatihan Pembuatan Surat Administrasi dengan Microsoft Word untuk Aparatur Desa Banyoneng Laok, Kecamatan Geger, Kabupaten Bangkalan - Septiana, Aldila; Akbar, Muhammad Almer Ghazian (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This community service program aims to provide training in making cover letters using MS Word to Banyoneng Laok Village officials, Geger District, Bangkalan Regency. The service method is carried out through organizing training events involving DPL and a team of KKN students as companions. During the event, participants showed high enthusiasm and were active in participating. The explanations and reflections from the DPL and the KKN student team were considered clear and interesting by the participants, making it easier to understand and apply the material. In addition, a tutorial summary is available to make it easier for participants to remember the steps for preparing a village administration letter. Interesting requests also emerged from participants, who asked for video tutorials to be made as additional reference material. Thus, this activity succeeded in improving technical skills and administrative knowledge for Banyoneng Laok Village officials.